KETIDAKHARMONISAN KOMUNIKASI DALAM KELUARGA PADA PEMBENTUKAN PRIBADI ANAK (PENDEKATAN HUMANISTIK) - Dyah Ayu Nidyansari (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2018)
The relationship of a family is highly influenced by the role of the husband and wife, as a parent their views and their way of educating their kids will lead to the well-being of the family. This research aims to determine the importance of communicating is in a family and how it could mold the child to a non-harmonious family and disharmony communication in the family on the developing o children personality deviant. The method used in this research is a qualitative method of data collection techniques with in-depth interviews on three sources and data analysis techniques in this research used the Huberman. Data analysis was conducted qualitatively and studied using interpersonal communication theory from Alvonco, J. The result of this research is, that interpersonal communication between children and parents is needed in the family, poor communication within the family can cause divisions among family members and make members close to communicate with each other so that the needs of a child in the family is not harmonious unfulfilled so children are very easy to fall into the negatives and have a deviant person in the community.